Water Impact Calculator: A decision support tool for irrigation scheduling - Garg, Kaushal K. (2025)
Water is one of the most critical inputs in agriculture, yet it is also one of the most mismanaged resources. In many farming systems, irrigation is scheduled based on fixed calendars or farmers’ intuition rather than actual crop water needs. This often results in over-irrigation, leading to waterlogging, nutrient leaching, and inefficient energy use, or under-irrigation, causing moisture stress and yield losses. With increasing water scarcity, uncertain rainfall, and growing pressure on water resources, there is an urgent need for smart and efficient irrigation management systems. To address this challenge, the Water Impact Calculator (WIC) has been developed using a field water budget-based approach. This innovative tool enables need-based irrigation scheduling by integrating field conditions, weather data, and crop requirements. Users simply input basic information such as soil type, land slope, sowing date, and crop duration. The tool then incorporates rainfall and meteorological data to estimate potential evapotranspiration and crop water demand accurately. WIC continuously evaluates the soil water balance and checks whether sufficient water is available in the vadose zone to meet crop requirements. When moisture levels fall below critical thresholds, the system issues a real-time irrigation alert, prompting timely and precise water application. A key strength of WIC lies in its adaptive feedback mechanism: if actual water application differs from the recommendation, the tool recalibrates subsequent irrigation requirements accordingly. Importantly, WIC offers a cost-effective solution for farmers who cannot afford expensive soil moisture sensors or digital automation systems. By relying on easily available field and weather information, it makes precision irrigation accessible to small and marginal farmers as well. This dynamic, data-driven approach enhances water use efficiency, reduces wastage, and optimizes irrigation frequency and volume. By integrating WIC into farm management, irrigation practices can move closer to precision agriculture, where every drop of water is applied judiciously. Ultimately, this tool empowers farmers, water managers, and policymakers with actionable insights, contributing to sustainable water resource management, improved crop productivity, and greater climate resilience in agriculture.